Pengaruh Motivasi Keja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan di Pabrik Gula Modjopanggoong Tulungagung - Miftahul Ilmi (BIMA : Journal of Business and Innovation Management, 2020)
Modjopanggong sugar factory is a company engaged in the sugar industry engaged in the field of sugar cane milling (making sugar) which is the locomotive of the regional and national economy.This study aims to determine the effectthe effect of work motivation and work discipline on employee work productivity at PG Modjopanggoong Tulungagung. The method used in this study is a quantitative research method and uses a causal or causal approach. The total sample of 136 employees using simple random sampling technique. Data collection techniques using a questionnaire.Hypothesis test uses t test, R test and F test. The results of this study indicate that (1) Work Motivation has a partial effect on employee work productivityin PG Modjopanggoong Tulungagung Work discipline has a partial effect on work productivity in PG Modjopanggoong Tulungagung (3) Work motivation and work discipline simultaneously influence work productivity in PG Modjopanggoong Tulungagung.